Guia de identificação de plantas arbóreas do Parque Natural da Água Vermelha “João Câncio Pereira” em Sorocaba - Caetano, Giovana Sgobbi (Universidade Federal de São Carlos, 2024)
The forest remnants occupy only 11.1% of the municipality of Sorocaba, due to the fragmentation of the natural environment, therefore, urban parks have become important refuges for plant biodiversity. These green areas improve the quality of life of the population, providing leisure, physical activities and contributing to nature conservation. The paper aims to discover the botanical diversity of the Água Vermelha “João Câncio Pereira” Natural Park in the city of Sorocaba (state of São Paulo) and express it in images and information through a guide with educational purposes that aims to promote the knowledge of tree species among people who visit the park, contributing to the local flora appreciation, overcoming botanical imperception and encouraging the preservation of the natural environments. The park's tree species were extensively surveyed, such as trees with trunks with a diameter at breast height (DBH) greater than 20 centimeters in the park's visitor areas, such as walking trails and flat soils. The collections were carried out from September to December 2023 and, at each collection, the branches were transported to the Federal University of São Carlos (UFSCar) in Sorocaba, where they were pressed and dried in an oven with an approximate temperature of 60ºC. After drying, each specimen was identified to species level with the help of literature and botanical experts. In total, 56 tree plants from 22 species and 10 different families were sampled; 14 are characterized as native to Brazil, 5 as cultivated, 2 as naturalized, and one was able to identify only the gender. The Fabaceae family had the largest number of species (9); Mangifera indica (mango tree), Syzygium cumini (jambolão) and Peltophorum dubium (canafístula) had the highest number of specimens, 9, 8 and 7, respectively. The most common pollination syndrome was melitophilia; the most common seed dispersal syndrome was zoochory, mainly by small mammals. In addition to these data, the guide presents photos and information about the leaves, trunk, flowers and fruits of the species, their commercial uses and the conservation status of the species according to The International Union for Conservation of Nature’s Red List of Threatened Species. The guide also has an interactive aerial view map pointing out the 56 tree plants, in which the reader is directed to the page of the respective species; a glossary with botanical terms and symbols for better understanding by visitors.
Tree identification guide in the Água Vermelha “João Câncio Pereira” Natural Park in Sorocaba
Keywords: parque urbano; angiospermas; conservação; biodiversidade; guia educativo; urban park; angiosperms; conservation; biodiversity; educational guide; CIENCIAS BIOLOGICAS::BOTANICA::TAXONOMIA VEGETAL